Bound states of the Duffin-Kemmer-Petiau equation with a mixed minimal-nonminimal vector cusp potential - de Castro, A. S. [UNESP] (Iop Publishing Ltd, 2011)
The problem of spin-0 and spin-1 bosons subject to a general mixing of minimal and nonminimal vector cusp potentials is explored in a unified way in the context of the Duffin-Kemmer-Petiau theory. Effects on the bound-state solutions due to a short-range interaction are discussed in some detail.